A review of the associations between single nucleotide polymorphisms in taste receptors, eating behaviors, and health. Issue 2 (22nd January 2018) - Chamoun, Elie; Mutch, David M.; Allen-Vercoe, Emma; Buchholz, Andrea C.; Duncan, Alison M.; Spriet, Lawrence L.; Haines, Jess; Ma, David W. L.; ,
ABSTRACT: Food preferences and dietary habits are heavily influenced by taste perception. There is growing interest in characterizing taste preferences based on genetic variation. Genetic differences in the ability to perceive key tastes may impact eating behavior and nutritional intake. Therefore, increased understanding of taste biology and genetics may lead to new personalized strategies, which may prevent or influence the trajectory of chronic disease risk. Recent advances show that single nucleotide polymorphisms (SNPs) in the CD36 fat taste receptor are linked to differences in fat perception, fat preference, and chronic-disease biomarkers. Genetic variation in the sweet taste receptor T1R2 has been shown to alter sweet taste preferences, eating behaviors, and risk of dental caries. Polymorphisms in the bitter taste receptor T2R38 have been shown to influence taste for brassica vegetables. Individuals that intensely taste the bitterness of brassica vegetables ("supertasters") may avoid vegetable consumption and compensate by increasing their consumption of sweet and fatty foods, which may increase risk for chronic disease. Emerging evidence also suggests that the role of genetics in taste perception may be more impactful in children due to the lack of cultural influence compared to adults. This review examines the current knowledge of SNPs in taste receptors associated with fat, sweet, bitter, umami, and salt taste modalities and their contributions to food preferences, and chronic disease. Overall, these SNPs demonstrate the potential to influence food preferences and consequently health.